Biosocial correlates of perinatal mortality in rural lucknow - Idris, M Z; Saran, Nanak; Jain, Savita; Misra, P K (Indian Journal of Community Health, 1994)
Six hundred and forty three consequltive pregnancies occurring between March to February, 90 in the Mohanlalganj community Development Block of Lucknow District, were registered during second trimester and fotlowed-up till seven days crfte r delivery, for study of perinatal mortality and related blosoclal correlates. A total of 20 still births and 27 Neonatal deaths were recorded out of the six hundred forty nine newborns which included seven twins also. Overall Perinatal Mortality Rate was found to be 72.4 per thousand births. Perinatal Mortality was significantly high among twin deliveries (500 per thousand births), mothers aged below 18 and above 30 years (136.3 and 100 per thousand deliveries respectively), spacing less than IS months (113.4 per thousand deliveries). Gestation age below 28 weeks (1000 deaths per thoitsand births) and among primipara (112.6 per thousand births).